Efficient Pollution Regulation: Getting the Prices Right: Reply - Muller, Nicholas Z; Mendelsohn, Robert (American Economic Review, 2012)
Fraas and Lutter raise two important points in their comment on Muller and Mendelsohn (2009): How to design policies for sources that yield negative marginal damages? How does statistical uncertainty in the marginal damages affect the trading ratios across emitters? We address both issues in this response. JEL: H53, Q53, Q58